2019
DOI: 10.17942/sted.381207
|View full text |Cite
|
Sign up to set email alerts
|

Üniversite Öğrencilerinde Akıllı Telefon Bağımlılığı İle Servikal Bölge Ve Üst Ekstremite Ağrısı Arasındaki İlişki

Abstract: The study was carried out to determine the opinions of mothers whose infants were staying in the Neonatal Intensive Care Unit (NICU) on staying with baby during care and treatment, participation in the procedures, and family centered care in the unit. Materials and Method: The data of this descriptive research were obtained through a questionnaire from 63 mothers whose babies have been hospitalized at the NICU of a university hospital in Istanbul between January and June 2017. Findings: It was determined that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0
10

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 22 publications
1
6
0
10
Order By: Relevance
“…Akıllı telefonlarda bulunan ağrı uygulamalarının içeriği ve kendi kendini yönetme işlevselliği günümüzde araştırılan konular arasındadır. Yapılan bazı çalışmalarda postür düzeltme uygulamalarının üniversite öğrencilerinde öz-yönetim fonksiyonunu, ağrı eğitimini ve kendi kendini izleme becerisini sağladığı gösterilmiştir [14][15][16]. Diğer yönden eğitimcilerin büyük çoğunluğunda özellikle bel bölgesinde olmak üzere çeşitli vücut bölümlerinde ağrılar ve kas-iskelet sistemi problemleri vardır [17,18].…”
Section: Methodunclassified
See 2 more Smart Citations
“…Akıllı telefonlarda bulunan ağrı uygulamalarının içeriği ve kendi kendini yönetme işlevselliği günümüzde araştırılan konular arasındadır. Yapılan bazı çalışmalarda postür düzeltme uygulamalarının üniversite öğrencilerinde öz-yönetim fonksiyonunu, ağrı eğitimini ve kendi kendini izleme becerisini sağladığı gösterilmiştir [14][15][16]. Diğer yönden eğitimcilerin büyük çoğunluğunda özellikle bel bölgesinde olmak üzere çeşitli vücut bölümlerinde ağrılar ve kas-iskelet sistemi problemleri vardır [17,18].…”
Section: Methodunclassified
“…Postür düzeltme uygulaması olarak öğretmenler akıllı telefonlarına "Text Neck-Forward Head Posture Correction" (IOS ve Android), "Neck & Spine Wellness-Neck Posture Corrector" (Android), "Text Neck Indicator-Lite" (Android) ve "Text Neck Relief ve NeckGuard (IOS)" uygulamalarından herhangi birini yüklediler. Bu uygulamaların genel özelliği; kullanıcı telefonunu başını öne eğerek kötü bir açıda belirli bir süre kullandığında kullanıcıya görsel ve/veya işitsel uyarı göndermek ve kullanıcının postürünü düzeltmesini hatırlatmaktır [14][15][16]. Ücretsiz kullanılabilen bu uygulamalar akıllı telefon işletim sistemine bağlı olarak akıllı telefonlara yüklenebildiğinden tek bir uygulama kullanılması yerine birkaç uygulama içerisinden akıllı telefon kullanıcısına en uygun gelenin seçilmesine olanak tanınmıştır.…”
Section: Materyal Ve Metotunclassified
See 1 more Smart Citation
“…However, the transformation of this widespread use of smartphones to addiction has been reported to have negative effects on the feeling of satisfaction with life, happiness levels, and subjective well-being of young people (Kozan, Kavaklı, & Cutter, 2019;Çelik, 2018;Lepp, Barkley and Karpinski, 2014;Park and Lee, 2012). Apart from the stated psychological problems, hand and neck dysfunctions, headache, and poor sleep quality physiological problems are also among the negative effects of smartphone addiction (Sülün, Günay, Sarman and Dertli, 2020;Günal and Pekçetin, 2019;Koças and Şaşmaz, 2019;Randjelović, Stojiljković, Radulović, Stojanović and Ilić, 2019;Keskin Ergan, Başkurt and Başkurt, 2018;Yorulmaz, Kıraç and Sabırlı, 2018;Demirci, Akgönül and Akpınar, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…University students' excessive use of social media or the internet can have an adverse impact on their time use and lead to problems in their work, school (Suhail and Bargees, 2006), and social life (Tyagi and Soni, 2019), which indicates a relationship with OB. Previous researchers showed that smartphone addiction was associated with depression, loneliness, physical problems, and poor academic performance (Alhassan, Alqadhib, Taha et al, 2018;Güzeller and Coşguner, 2012;Rupert and Hawi, 2016;Günal and Pekçetin, 2019).…”
mentioning
confidence: 99%